2008
DOI: 10.1200/jco.2006.10.4190
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel in Combination With Doxorubicin and Cyclophosphamide As Adjuvant Treatment for Early Node-Positive Breast Cancer: A Cost-Effectiveness and Cost-Utility Analysis

Abstract: The use of adjuvant TAC rather than FAC for node-positive early breast cancer patients is cost effective, despite the increased drug and toxicity treatment costs, and when primary G-CSF prophylaxis is given to all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 17 publications
2
32
1
Order By: Relevance
“…Economic evaluations for other docetaxel-based adjuvant chemotherapy regimens for breast cancer have also been conducted 23,[42][43][44][45][46] . Compared with fac (5-fluorouracil-doxorubicin-cyclophosphamide), tac (docetaxel-doxorubicin-cyclophosphamide) administered with and without prophylactic g-csf was found to be a cost-effective strategy in a number of jurisdictions 36,37,39,40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic evaluations for other docetaxel-based adjuvant chemotherapy regimens for breast cancer have also been conducted 23,[42][43][44][45][46] . Compared with fac (5-fluorouracil-doxorubicin-cyclophosphamide), tac (docetaxel-doxorubicin-cyclophosphamide) administered with and without prophylactic g-csf was found to be a cost-effective strategy in a number of jurisdictions 36,37,39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…From a Canadian health care system perspective, Au et al 42 reported cost-utility ratios of $46,003 and $18,506 per qaly gained with and without prophylactic g-csf at a 10-year horizon, and Mittmann et al 43 reported cost-utility ratios of $13,044 and $6,848 per qaly gained at a lifetime horizon. From a U.K. National Health Service perspective, Wolowacz et al 44 Compared with fec100 (5-fluorouracil-epirubicin-cyclophosphamide), fec-d (5-fluorouracil-epirubicin-cyclophosphamide-docetaxel) was also found to be a cost-effective strategy 23,46 . From a Canadian health care perspective, Younis et al 23 reported a cost-utility of $14,612 per qaly at a 10-year horizon, and from a French hospital perspective, Marino et al 46 reported a cost-utility of €9,665 per qaly at a 5-year horizon.…”
Section: Discussionmentioning
confidence: 99%
“…A published utility score of 0.79 for patients with early breast cancer in remission was used 14 . That utility score was calculated from European Organisation for Research and Treatment of Cancer quality-of-life questionnaire (qlq-C030) data for 929 patients in the BCIRG001 clinical trial who had completed chemotherapy and who had not experienced a relapse 10 , using a published algorithm 21 .…”
Section: Health Utility Assumptionsmentioning
confidence: 99%
“…Utility decrements for local (-0.09) and distant recurrence (-0.29) were calculated from Wolowacz et al 14 by subtracting the respective utility scores reported for local and distant recurrence from the utility score reported for remission. These utility decrements are applied in the model according to the proportion of patients in each treatment arm experiencing local or distant recurrence respectively.…”
Section: Health Utility Assumptionsmentioning
confidence: 99%
“…50,51 When a more effective, but more myelosuppressive, regimen is appropriate the use of this regimen with growth factor support appears cost effective as well. 52 Another recent analysis of costeffectiveness utilising the payer's perspective in Europe has concluded that secondary prophylaxis with antibiotics is more cost-effective than a combined strategy of antibiotics and G-CSF. 53 …”
Section: Cost-effectiveness Of Prophylaxis With Growth Factorsmentioning
confidence: 99%